Site pages

Current course

Participants

General

Topic 1

Topic 2

Topic 3

Topic 4

Are you confused? Maybe a few more examples will help. Let's try this one:

In this case, you will want to get the variable ( y ) by itself. But you can see that ' - 8' is beside the y and you must get rid of that to get y by itself. To get rid of - 8, you need to do the opposite: add 8 to both sides of the equation, like this:

Now the 8's cancel out (because - 8 + 8 = 0) and you have y by itself on the left side of the equation. When you do the addition on the right side, you find the answer:

Here's another example with addition. You can see that it starts off with a variable (e) and + 33. You will need to do the opposite (- 33) on both sides of the equation, like this:

One more example, this time starting with subtraction:

Hint: one of the neat things about algebra is that you can always check yourself to see if you're right. Just substitute the answer that you get for the variable, back into the original equation, to see if it works. In this last example, erase the variable "s" in the original equation (s - 14 = 6) and replace it with the number "20". This now gives you 20 - 14 = 6, which you know is true!

y - 8 = 17

In this case, you will want to get the variable ( y ) by itself. But you can see that ' - 8' is beside the y and you must get rid of that to get y by itself. To get rid of - 8, you need to do the opposite: add 8 to both sides of the equation, like this:

y - 8 + 8 = 17 + 8

Now the 8's cancel out (because - 8 + 8 = 0) and you have y by itself on the left side of the equation. When you do the addition on the right side, you find the answer:

y = 25

Here's another example with addition. You can see that it starts off with a variable (e) and + 33. You will need to do the opposite (- 33) on both sides of the equation, like this:

e + 33 = 40

e + 33 - 33 = 40 - 33

e = 7

e + 33 - 33 = 40 - 33

e = 7

One more example, this time starting with subtraction:

s - 14 = 6

s - 14 + 14 = 6 + 14

s = 20

s - 14 + 14 = 6 + 14

s = 20

Hint: one of the neat things about algebra is that you can always check yourself to see if you're right. Just substitute the answer that you get for the variable, back into the original equation, to see if it works. In this last example, erase the variable "s" in the original equation (s - 14 = 6) and replace it with the number "20". This now gives you 20 - 14 = 6, which you know is true!

Last modified: Tuesday, 26 July 2011, 5:04 PM